(untitled) (Fiep Bulletin - online, 2014)
The quality of life is an outcome of mutual effect of social, health, economical and environmental conditions concerning humans and social development. On one side represents objective conditions for good life and on the other side its subjective experience. For our investigation we chose the assessment of 23 quality of life factors importance by SQU ALA – standardized questionnaire. 247 university students (64.8 % of men and 35.2 % of women) with different health status (74.5 % healthy and 25.5 % with some health impairment) participated in our research. Results have been differentiated by health status sport participation. Psychological, social and emotional and even physical quality of life indicators concerning to external and internal facts of everyday reality significantly assumed higher level quality of life for the healthy group of students with elite level of sport participation. Research is a part of grand project VE GA nr. 1/0915/13 with topic „Sport as a part of quality of life of people with disability“.